Analysis and Comparison of Gut Microbiome in Young Detection Dogs - Li, Zongjie; Sun, Qing; Li, Yuhao; Guan, Zhixin; Wei, Jianchao; Li, Beibei; Liu, Ke; Shao, Donghua; Mi, Rongsheng; Liu, Haixia; Qiu, Yafeng; Ma, Zhiyong (Frontiers in Microbiology, 2022)
The detection dogs are well-known for their excellent capabilities to sense different kinds of smells, which can play an important role in completing various searching and rescuing missions. Recent studies have demonstrated that the excellent olfactory function of detection dogs might be related with the gut microbes via the bidirectional communications between the gastrointestinal tract and brain. In the current study, the gut microbial communities of three breed types of detection dogs (Springer Spaniel, Labrador retriever, and German Shepherd) were studied and compared. Results revealed that the richness and diversity of gut microbiome German Shepherd dogs was significantly higher than the Labrador retriever dogs and the Springer Spaniel dogs. At the phylum level, the most predominant gut microbial communities of the detection dogs were comprised of Fusobacteriota, Bacteroidetes, Firmicutes, Proteobacteria, Campilobacterota and Actinobacteriota. At the genus level the most predominant gut microbial communities were comprised of Fusobacterium, Megamonas, Prevotella, Alloprevotella, Bacteroides, Haemophilus, Anaerobiospirillum, Helicobacter, Megasphaera, Peptoclostridium, Phascolarctobacterium, and Streptococcus. Howeover, the gut microbial communities of the three group dogs were also obviously different. The mean relative abundance of Fusobacterium, Prevotella, Alloprevotella, Megamonas, Bacteroides, and Phascolarctobacterium presented significant differences in the three groups. According to the portraits and characteristics of the gut microbiome in young detection dogs, multiple kinds of nutritional interventions could be applied to manipulate the gut microbiota, with the aim of improving the health states and the olfactory performances.